Neoadjuvant chemoradiotherapy for thoracic esophageal squamous cell carcinoma: does everyone need it? - D. A. Chichevatov; E. N. Sinev; A. E. Glukhov; O. M. Seliverstova (Сибирский онкологический журнал)
Objective. In accordance with clinical guidelines, neoadjuvant chemoradiotherapy (nCRT) is recommended as a beneficial option for treatment of thoracic esophageal squamous cell carcinoma (TESCC). However, some studies did not demonstrate potential benefits of nCRT. In this paper we compared treatment outcomes of surgery alone with preoperative CRT followed by surgery. Material and methods. Group 1 (n=147) consisted of patients who underwent surgery alone. Group 2 (n=3,337) was formed in the framework of the present systematic review and meta-analysis (15 publications captured 20 separate subgroups for analysis). Patients of group 2 received nCRT followed by esophagectomy. Overall survival (OS) and median OS were estimated. Results. The median OS was reached in group 1 and in 12 separate subgroups of group 2 (2310 of 3337 patients). In groups 1 and 2 the OS median estimates were 31.0 and 28.1, respectively (p=0.873). Respective 3-year and 5-year OS were 0.49 vs 0.48 (p=0.425) and 0.37 vs 0.41 (p=0.228). The median OS was not reached in 8 separate subgroups of group 2 (1027 of 3337 patients). In this case, group 2 patients had significantly higher 3- and 5-year OS compared to group 1 patients: 0.69 vs 0.49 (p=0.000) and 0.60 vs 0.37 (p=0.000), respectively. Pathological complete response to nCRT was associated with better survival. conclusion. nCRT is not appropriate for all patients with TESCC. Improved overall survival may be achieved in patients with a high grade of pathological tumor response to neoadjuvant treatment. Selective administration of nCRT based on highly probable prediction of complete tumor response seems promising. This concept needs further research.